Influence of Coated Electrode in Nanopowder Mixed EDM of Al–Zn–Mg–Si3N4 Composite - G. Anbuchezhiyan; R. Saravanan; R. Pugazhenthi; Kumaran Palani; Vamsi Krishna Mamidi (Advances in Materials Science and Engineering, 2022)
Machinability investigation of new material is one of the mandatory investigations to complete the purpose of creation of it. Electrical discharge machining (EDM) is one of the promising unconventional machining processes for highly accurate machining performance in difficult-to-cut material even machining complicated profiles. The powder-mixed EDM and nanopowder-mixed EDM are the improved versions of the EDM. The Al–Zn–Mg composite is reinforced with Si3N4 (9 wt. %) for meeting automotive and marine applications. The aluminium nanoparticles enhanced deionised water was used in NPMEDM. The nickel-coated brass and uncoated brass tube electrode were considered for the investigation. Pulse on time (µs), voltage (V), input current (A), and capacitance (nF) were independent variables and varied at 3 levels. The microhole machining performance with a coated and uncoated electrode was investigated. The L18 orthogonal array involved in the experimental design, material removal rate, and electrode wear rate were analysed. The SEM analysis was employed in the surface morphological study of electrodes before and after machining. The input parameters were optimised for the coated electrode for the responses of MRR and EWR.